Variasi Koefisien Kekasaran Manning (n) pada Flume Akrilic pada Variasi Kemiringan Saluran dan Debit Aliran - Putro, Haryono; Hadihardaja, Joetata (Department of Civil Engineering, Diponegoro University, 2013)
Based on the book of open channels hydraulics by Ven T. Chow (1988) mentioned that the big problems in application Manning equation is determine of roughness coefficien n, because there is no certain way to choose value of n. At the current knowledge, choosing the actual value of n is estimated flow resistance on certain channels, that really can not be taken into specific value. The purpose of this study is experimentation to describe the differences Manning roughness coefficient (n) at the same material of channel by a different channel slope and discharge. The method used is by modeling the physical channel with a width of 15cm and depth of 20cm with akrilic material thickness of 0.5 cm. Flow in a channel by channel basis slope variation 0.0087; 0.0175; 0.0349 and 0.0524. With the discharge varies from 1 to 4.5 liters / sec. The results of the analysis showed there vairiasi n values between 0.006 to 0.032.